Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.3* The Natural Exponential Function - 6.3* Exercises: 3

Answer

(a) $e^{-ln2}=\frac{1}{2}$ (b) $e^{ln(lne^{3})}=3$

Work Step by Step

The exponential function is defined by if $e^{x}=y$ then $x =lny$. (a) $e^{-ln2}=\frac{1}{2}$ (b) Let $lnz=e^{ln(lne^{3})}$ $z=ln(e^{3}) = 3lne$ $=3$ Hence, $e^{ln(lne^{3})}=3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.